2021
DOI: 10.30773/pi.2021.0016
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Effects of the COVID-19 Outbreak in Middle School Students and Caregivers

Abstract: Objective To investigate the traumatic effects of the COVID-19 pandemic on middle-school students and their parents. Methods This epidemiological cross-sectional study was conducted with middle-school students in Denizli. A questionnaire consisting of the IES-R, CRIES-13 and a sociodemographic data form was delivered online. A total of 1059 participants who fully completed the questionnaire were included for analysis. Results The IES-R total and subdimension scores and the CRIES-13 scores were found to be sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…Stress could negatively affect how parents approach their children (Silliman Cohen & Bosk, 2020). In the literature, similar to the results of our study, it was reported that parental stress had negative effects on the mental state of children (Chung et al, 2022; Terzioğlu & Büber, 2021). Parents under stress have trouble understanding and responding to their children’s needs sensitively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Stress could negatively affect how parents approach their children (Silliman Cohen & Bosk, 2020). In the literature, similar to the results of our study, it was reported that parental stress had negative effects on the mental state of children (Chung et al, 2022; Terzioğlu & Büber, 2021). Parents under stress have trouble understanding and responding to their children’s needs sensitively.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted in Spain, it was revealed that more parenting stress was experienced during the COVID-19 pandemic and this stress led to child mental health problems (Çimke, Gürkan, & Yorulmaz, 2021; Romero et al, 2020). In their study, Terzioğlu and Büber (2021) reported that the increase in the psychological trauma experienced by parents during the pandemic increased the trauma of their children. In a study conducted with 1,771 adolescents during the COVID-19 pandemic, it was stated that 28.3%–30.8% of adolescents had symptoms of anxiety and depression (Ren et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, being a single parent during the COVID‐19 lockdown increased the prevalence of high psychological distress among caregivers, especially mothers (Marchetti et al, 2020), due to the lack of parental support from a partner (Mikolajczak et al, 2018). Correspondingly, during the pandemic, children of divorced families were at higher risk of developing psychological impairments (Terzioğlu & Büber, 2021). Indeed, highly distressed mothers might have been too overwhelmed by the situation to be available and responsive to their children's needs and to find appropriate ways to be supportive for them; this might have increased the likelihood that their children developed negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the review, almost half of the papers described the factors associated with mental health status due to COVID-19 pandemic. The major factors that have tendency to increase anxiety and depression were found to be restriction on movement, social distancing, school closures, low interaction with peers, educational status, smartphone and internet addiction, increased use of digital screens, continuous watching, listening, or reading news related to COVID 19, urban residency, family members or friends infected with coronavirus, being children of frontline health workers, level of anxiety, fearphysical injury fear, fear of separation, employment status, type of occupation, female gender, low social support, exposure to COVID-19 (Cohodes et al, 2021;Qi et al, 2020;Terzioğlu & Büber, 2021).…”
Section: Factors Associated With Mental Health Illnessesmentioning
confidence: 99%